2015
DOI: 10.5301/tj.5000230
|View full text |Cite
|
Sign up to set email alerts
|

Improving Physicians' Communication Skills and Reducing Cancer Patients' Anxiety: A Quasi-Experimental Study

Abstract: Our findings suggest the effectiveness of the communication skills training program with reference to patient anxiety levels. Given the potential gap between training and clinical impact, further studies investigating the effect of communication training on patient outcomes are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…Effective communication among cancer patients, survivors, caregivers, and providers facilitates shared decision making and fosters patient‐centered health outcomes . Such collaborative communication offers a wide range of benefits to the patients and their caregivers including timely reporting of clinical symptoms to their providers, decreasing anxiety and stress, improving satisfaction about the offered services, enhancing adherence to therapies, enabling informed decision making, and improving quality of life (QoL) . Effective PPC allows providers to discuss complex conditions, provide timely feedback to patients, and empower patients to report, assess, and manage psychosomatic symptoms …”
Section: Introductionmentioning
confidence: 99%
“…Effective communication among cancer patients, survivors, caregivers, and providers facilitates shared decision making and fosters patient‐centered health outcomes . Such collaborative communication offers a wide range of benefits to the patients and their caregivers including timely reporting of clinical symptoms to their providers, decreasing anxiety and stress, improving satisfaction about the offered services, enhancing adherence to therapies, enabling informed decision making, and improving quality of life (QoL) . Effective PPC allows providers to discuss complex conditions, provide timely feedback to patients, and empower patients to report, assess, and manage psychosomatic symptoms …”
Section: Introductionmentioning
confidence: 99%
“…The first authors of the included articles were affiliated with institutes from the following countries: the USA n = 14 [1, 2, 6, 9, 10, 12, 13, 16-18, 20, 32, 34, 42] , Switzerland n = 7 [3-5, 8, 31, 37, 44] , the UK n = 5 [7,21,30,39,46] , Germany n = 5 [27,28,40,48,49] , Australia n = 5 [11,14,15,19,29] , Japan n = 4 [22][23][24][25] , Belgium n = 4 [26,33,35,36] , the Netherlands n = 1 [47] , China n = 1 [41] , Taiwan n = 1 [45] , Italy n = 1 [38] and Canada n = 1 [43] . Most authors worked together in eight research groups, and three articles were co-authored by members of separate research groups.…”
Section: Included Studiesmentioning
confidence: 99%
“…b. While almost one-fifth of the included articles n = 9 [1,6,7,13,14,24,25,33,38] provided no information on supervision or booster sessions, most indicated that their CST programmes were not supplemented by supervision or booster sessions n = 27 [2, 9, 10, 12, 15-17, 19*, 20*, 21-23, 26*, 29, 30, 32, 34, 35*, 36, 39, 41, 42, 43*, 45-47, 49] . c. Half-day and 1-day training are equally expensive, but 1 day of training yields better results, thus, favouring the latter [19*] .…”
mentioning
confidence: 99%
“…23 Patient anxiety has been shown to decrease when physicians show affective communication 24 and when physicians have been trained to recognise and manage their own emotional reactions in their relationships with patients. 25 To summarise, the research question addressed in this paper is whether physicians' stress, training, experience, and alexithymia, and patients' sadness, anxiety, and alexithymia are related to physicians' use of defence mechanisms during patient-physician communication in cancer care. The goal is to generate new hypotheses to increase the quality of research and/or training to move from standardised to more flexible communication in cancer care.…”
Section: Patient-related Factorsmentioning
confidence: 99%
“…However, physicians tend to provide more in‐depth empathetic responses to fear than to sadness . Patient anxiety has been shown to decrease when physicians show affective communication and when physicians have been trained to recognise and manage their own emotional reactions in their relationships with patients …”
Section: Introductionmentioning
confidence: 99%